Capitalism's New Clothes Enterprise, Ethics and Enjoyment in Times of Crisis - Cremin, Ciara (Pluto Press, 2011)
From broadsheet newspapers to television shows and Hollywood films, capitalism is increasingly recognised as a system detrimental to human existence. Colin Cremin investigates why, despite this de-robing, capitalism remains a powerful and seductive force. Using materialist, psychoanalytic and linguistic approaches, Cremin shows how capitalism, anxiety and desire enter into a mutually supporting relationship. He identifies three ways in which we are tied in to capitalism - through a social imperative for enterprise and competition; through enjoyment and consumption; and through the depoliticisation of ethical debate by government and business. Capitalism's New Clothes is ideal for students of sociology and for anyone worried about the ethics of capitalism or embarrassed by the enjoyments the system has afforded them.